Perawatan Spiritual pada Pasien Kanker Payudara - Ni'mah Mufidah; Anggorowati Anggorowati; Suhartini Ismail (Jurnal Keperawatan Silampari, 2023)
This study aims to get an overview of Islamic spiritual interventions that can be applied to breast cancer patients. The research method used in this research is scoping review based on the Arksey and O'Malley way by searching articles through Databased: EBSCO, SpringerLink, Pubmed, ProQuest, Science Direct, and Scopus and using the keywords "spiritual care intervention" or "spiritual intervention" AND "nurse" AND "breast cancer." The results showed that the articles reviewed, namely articles published from 2017 to 2022 with the specified criteria, were found in 11 pieces. In conclusion, Islamic spiritual interventions that can be applied to breast cancer patients include dhikr therapy, spiritual counseling, nursing care based on support-based spiritual care models, religious-spiritual psychotherapy, and group spiritual interventions based on the Koran and Islam. Keywords: Spiritual Care Intervention, Breast Cancer, Nurse